Qard Financing And Stability Of Islamic Rural Banks - Rahmat, Rahmat; Widarjono, Agus (JPS (Jurnal Perbankan Syariah), 2025)
The purpose of this study is to analyze the impact of Qard financing, market competition, internal bank factors and macroeconomic conditions on the stability of Islamic rural banks (IRBs) in Indonesia. This study analyzed as many as 123 banks that disbursed Qard financing in the 2015-2023 period using quarterly data. The analysis method used is panel data regression with an unbalanced data panel. This research also categorised IRBs into two groups: large and small. The study's results found that Qard financing has a negative effect on the stability of IRB. However, a large IRB faces a negligible risk compared to a small IRB in terms of distributing Qard financing, which reduces its stability. CAR, FDR and GDP have a positive effect on the stability of BPRS, while Assets, BOPO, NPF and COVID-19 have a negative effect on the stability of BPRS. The findings of this study have both theoretical and practical implications. From a theoretical perspective, although Qard financing reduces stability, it must still be distributed by IRB to achieve the goals of Maqasid Sharia. From a practical point of view, IBR must strengthen its fundamentals, such as capital and efficiency, to strengthen its stability.